Effect of CaO/Fe2O3 on ash fusibility during petroleum coke gasification and combustion. (1st January 2023) - Xiong, Qing-an; Huang, Youjian; Li, Jiazhou; Zhang, Yuming; Zhang, Wei
Highlights: Effect of CaO/Fe2 O3 on petroleum coke ash fusibility are studied. AFTs showed different performances in reducing and oxidizing atmospheres. The synergy effect of fusible and refractory minerals prevented the AFTs reduction. Abstract: Ash fusibility is closely related to ash melting, sintering and slagging, which is commonly used to guide the utilization of petroleum coke in boiler and gasifier. Calcium (Ca) and iron (Fe) show significant influence on the ash fusibility of petroleum coke. To quantify the influence of CaO/Fe2 O3 mass ratio on petroleum coke ash fusibility, ash fusion temperatures (AFTs) analysis, X-ray diffraction (XRD), and FactSage were applied to investigate the characteristics of petroleum coke ash fusibility with various CaO/Fe2 O3 mass ratios. The results showed that AFTs were closely associated with the CaO/Fe2 O3 ratio and showed different performances in different atmospheres. In the reducing atmosphere, with the increasing of CaO/Fe2 O3 ratio, the AFTs presented in turn a rapid decrease (from 0 to 2) and a smooth region (from 2 to ∞). The rapid decrease of AFTs was mainly attributed to the disappearance of high-melting point coulsonite (FeV2 O4 ) and the formation of low temperature eutectics anorthite (CaAl2 Si2 O8 ) and gehlenite (Ca2 Al2 SiO2 ). The formation of high-melting point calcium orthosilicate (Ca2 SiO4 ) inhibited the formation of CaAl2 Si2 O8 /Ca2 Al2 SiO2 to keep the AFTs at a stable level. In the oxidizing atmosphere, with the increasing of CaO/Fe2 O3 ratio, the AFTs presented in turn a rapid decrease (from 0 to 1), a smooth region (from 1 to 5), and a fast decrease once again (from 5 to ∞), respectively. The decline of AFTs was attributed to the substitution of NiFe2 O4 by fusible minerals (Ca2 V2 O7 /CaAl2 Si2 O8 ). The synergy effect of the refractory SiO2 and fusible minerals prevented the further decline of the AFTs.